EVALUATION OF APPROPRIATE USE OF ANTIFUNGAL THERAPY IN A TERTIARY CARE HOSPITAL - Islahudin, Farida; Mohd, Siti Fatimah Radiyah; Lai, Yin Key (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSTRACT Objective: Appropriate use of antifungal therapy has becoming a worrying issue since misuse of antifungal may contribute to the emergence and global increase in antifungal resistance. Use of a more standardized approach in identifying appropriate use is required in an attempt to reduce the risk of resistance. The study assesses the appropriate use of antifungal therapy in a local tertiary care hospital. Methods: It was conducted as a retrospective study based on patients prescribed antifungals for the past 1 year. Results: The A total of 135 patients were included in the study. The majority of the patients were Malay (n=77, 57%), followed by Chinese (n=39, 28.9%), Indians (n=11, 8.1%) and others (n=8, 5.9%). The mean age of patients was 57.5Â±16.58 years. The mean duration of admission was 29.39Â±21.85. Overall assessment of antifungal use demonstrated that antifungal therapy was appropriate in 85 (44.7%) cases, debatable in 34 (17.9%) and inappropriate in 71 (37.3%) cases (p=0.000015). There was a significantly high number of inappropriate azole use (p=0.0001) in the study population. The most common type of azole used was fluconazole. Further analyses identified that demographic factors that affected the duration of admission of those that survived were age, number of medication and number of antifungals. Duration of admission increased with increasing age (r=0.219, p=0.044), increase in medication (r=0.333, p=0.0019) and increase in number of antifungal treatment given (r=0.239, p=0.027). Conclusion: This work demonstrated the need for a closer or more stringent efforts in reducing inappropriate antifungal use. Keywords: Appropriateness, Antifungal therapy, Fungal infections.